Utilitarianism for infinite utility streams: Summable differences and finite averages - Adam Jonsson; Mark Voorneveld (Stockholm School of Economics, The Economic Research Institute (EFI), 2014)
This paper provides axiomatic descriptions of social welfare relations, defined on infinite streams of utility, that are consistent with the utilitarian criterion on subsets where maximizing aggregate utility has a clear interpretation: the streams, or their differences, are summable. Besides standard assumptions on efficiency, equity and interpersonal comparability, two axioms are introduced and shown to be necessary and sufficient. A more general version of one axiom suffices to distinguish streams with different long-run averages.
Keywords: D63; D70; D90; 330; intergenerational equity; aggregating infinite utility streams; ethical social welfare relations